2017
DOI: 10.5194/gmd-10-4129-2017
|View full text |Cite
|
Sign up to set email alerts
|

Improved method for linear carbon monoxide simulation and source attribution in atmospheric chemistry models illustrated using GEOS-Chem v9

Abstract: Abstract. Carbon monoxide (CO) simulation in atmospheric chemistry models is frequently used for source-receptor analysis, emission inversion, interpretation of observations, and chemical forecasting due to its computational efficiency and ability to quantitatively link simulated CO burdens to sources. While several methods exist for modeling CO source attribution, most are inappropriate for regions where the CO budget is dominated by secondary production rather than direct emissions. Here, we introduce a majo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 50 publications
2
45
1
Order By: Relevance
“…Such characteristics make tagging CO feasible and tagged CO relatively reliable as a tracer of pollution plumes from regional to hemispheric scales. Tagged CO has been widely used in previous studies for various research purposes such as source attribution (Buchholz et al, 2016;Chen et al, 2009;Fisher et al, 2017;Granier et al, 1999;Liu et al, 2003;Park et al, 2009;Pfister et al, 2011Pfister et al, , 2004Protonotariou et al, 2013;Staudt et al, 2001) and inverse modeling (Arellano et al, 2004(Arellano et al, , 2006Heald et al, 2004;Pétron et al, 2004). Our goal in this study is to elucidate the regional sources contributing to observed CO concentrations within the troposphere over Korea during the KORUS-AQ campaign using the tagged CO algorithm that is implemented in the Community Atmosphere Model with chemistry (CAM-chem).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such characteristics make tagging CO feasible and tagged CO relatively reliable as a tracer of pollution plumes from regional to hemispheric scales. Tagged CO has been widely used in previous studies for various research purposes such as source attribution (Buchholz et al, 2016;Chen et al, 2009;Fisher et al, 2017;Granier et al, 1999;Liu et al, 2003;Park et al, 2009;Pfister et al, 2011Pfister et al, , 2004Protonotariou et al, 2013;Staudt et al, 2001) and inverse modeling (Arellano et al, 2004(Arellano et al, , 2006Heald et al, 2004;Pétron et al, 2004). Our goal in this study is to elucidate the regional sources contributing to observed CO concentrations within the troposphere over Korea during the KORUS-AQ campaign using the tagged CO algorithm that is implemented in the Community Atmosphere Model with chemistry (CAM-chem).…”
Section: Introductionmentioning
confidence: 99%
“…Sources apportioned by tagged CO are sensitive to many parameters such as emissions, transport, chemistry, and resolution in the CTM. These factors are important sources of model errors (Gaubert et al, 2016;Müller et al, 2018;Naik et al, 2013;Strode et al, 2015;Yan et al, 2016), which could lead to CO underestimation commonly seen in most global CTMs but have not been fully understood yet (Fisher et al, 2017;Shindell et al, 2006;Stein et al, 2014;Tilmes et al, 2015). To provide insights on the sensitivity of our findings on source contributions to the aforementioned factors, we conduct an ensemble of model simulations with different model configurations and report the range of estimates of the source contributions from these simulations.…”
Section: Introductionmentioning
confidence: 99%
“…For CO, biomass burning plays an important role, as the main driver of the CO seasonal and interannual variability across the Southern Hemisphere (Edwards et al, 2006a, b). Overall, total CO in Australia is dominated by non-methane volatile organic carbon (NMVOC) and CH 4 oxidation (Té et al, 2016;Fisher et al, 2017), with negligible influence from anthropogenic emissions (Zeng et al, 2015). While prior work has provided some constraints on Australia's greenhouse-gas sources, both these studies and others have shown lingering differences between modelled and measured concentrations, implying that some sources of greenhouse gases in Australia remain missing or underestimated (Fraser et al, 2011;Loh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We use regional tracers from the CO simulation to identify sources of observed enhancements recorded in the TCCON data. Because we are interested in the sources of variability rather than absolute concentrations, we first correct a known low bias in the GEOS-Chem CO simulation, driven at least in part by a high bias in global OH [27]. We calculate an offset using a weighted least squares fit of the GEOS-chem output to the TCCON data, computed only on days when both model and observations suggest the site is sampling clean background air from the Pacific.…”
Section: Geos-chem Tagged Tracer Simulationsmentioning
confidence: 99%
“…The offline CO sim ulation is described by Fisher et al [27] and was run at 2 • × 2.5 • horizontal resolution with 47 vertical levels, from January 2016 until the end of May 2017. Fossil fuel emissions globally were taken from EDGAR (Emission Database for Global Atmospheric Research) version 4.2 [28], with regional overwrites for Asia [29], Europe [30], Canada [31], the United States [32], and Mexico [33], along with biofuel emissions from Yevich and Logan [34], ship emissions from the International Comprehensive Ocean-Atmosphere Data Set (ICOADS) [35] and Aviation Emissions Inventory Code (AEIC) [36].…”
Section: Geos-chem Tagged Tracer Simulationsmentioning
confidence: 99%